1996
DOI: 10.1073/pnas.93.7.2795
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of meiotic chromatin loop size by chromosomal position.

Abstract: MATERIALS AND METHODSChromosomal Localization of Insert in Transgenic Mice. Transgenic mice. The transgenic mice used in this study were derived from microinjection of cloned genomic DNA fragments containing the gene for the human major histocompatibility complex class I molecule HLA-B7. As described in detail elsewhere (9), line 18A was derived from microinjection of a 6.0-kb EcoRI/BamHI DNA fragment (fragment a), containing the wild-type gene and 0.66 kb of 5' and 2.0 kb of a 3' flanking DNA. Lines 30, 47, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(60 citation statements)
references
References 21 publications
3
57
0
Order By: Relevance
“…The presence of the glucocorticoid enhances the interaction by about threefold (compare lanes 3 and 4). These results are similar to those observed for interactions between several nuclear receptors and their partners (9,22). It should be pointed out that GR contains both ligand-dependent and ligand-independent activation domains.…”
Section: Baf250 Is An Integral Component Of Human Bafsupporting
confidence: 78%
“…The presence of the glucocorticoid enhances the interaction by about threefold (compare lanes 3 and 4). These results are similar to those observed for interactions between several nuclear receptors and their partners (9,22). It should be pointed out that GR contains both ligand-dependent and ligand-independent activation domains.…”
Section: Baf250 Is An Integral Component Of Human Bafsupporting
confidence: 78%
“…We have previously shown that loop size is constrained according to the chromosomal region (Heng et al, 1996). When the same DNA fragments were integrated into different regions of the chromosome, the loop size was significantly different.…”
Section: Resultsmentioning
confidence: 99%
“…Meiotic prophase in the mouse has become a model system for studying principles of chromosome organization. There are antibodies available to several of the SC proteins (Dobson et al, 1994), and the determinants of loop size have been the subject of several investigations (Heng et al, 1994(Heng et al, , 1996. The haploid genome size is 2.5 ϫ 10 9 bp.…”
Section: Resultsmentioning
confidence: 99%